2009
DOI: 10.1016/j.antiviral.2008.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Aurintricarboxylic acid inhibits influenza virus neuraminidase

Abstract: We previously identified a novel inhibitor of influenza virus in mouse saliva that halts the progression of susceptible viruses from the upper to the lower respiratory tract of mice in vivo and neutralizes viral infectivity in MDCK cells. Here, we investigated the viral target of the salivary inhibitor by using reverse genetics to create hybrid viruses with some surface proteins derived from an inhibitor-sensitive strain and others from an inhibitor-resistant strain. These viruses demonstrated that the origin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 63 publications
(79 reference statements)
0
77
0
Order By: Relevance
“…These findings highlight the possibility of mutations on residues other than catalytic or framework residues causing resistance to NAIs. In addition, the residue E276 is part of the hydrophobic pocket in the active site of NA needed to accommodate the pentyl side chain of OTV and this residue is highly conserved across all influenza A viruses (Hung et al, 2009). Furthermore, Tolentino-Lopez et al, (2013 showed that mutations outside the active site could affect the binding pattern of OTV and thus influence its resistance.…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the possibility of mutations on residues other than catalytic or framework residues causing resistance to NAIs. In addition, the residue E276 is part of the hydrophobic pocket in the active site of NA needed to accommodate the pentyl side chain of OTV and this residue is highly conserved across all influenza A viruses (Hung et al, 2009). Furthermore, Tolentino-Lopez et al, (2013 showed that mutations outside the active site could affect the binding pattern of OTV and thus influence its resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Algal polysaccharides (250 g/mL) were screened for their antiviral activities against influenza A/PR/8/34 (H1N1) virus using a cytopathic effect (CPE) reduction method in the Madin Darby canine kidney (MDCK) cell line as described previously (Hung, Tseng et al 2009;Wang, Zhang et al 2011 …”
Section: Antiviral Activitymentioning
confidence: 99%
“…2D). The I222 residue is highly conserved across all influenza A and B viruses and, together with R224, S246, and E276, forms the hydrophobic pocket of the active NA site (18). Of the 782 NA sequences from A(H5N1) viruses available on GenBank (accessed 15 January 2009), 24 (3%) had mutations at the I222 residue (I222T (15 strains), I222V (4 strains), I222L (2 strains), I222K (1 strain), I222F (1 strain), and I222M (1 strain)).…”
mentioning
confidence: 99%